A method to compute the inverse of a complex N-block tridiagonal Quasi-Hermitian matrix - Godfrin, Elena M. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Godfrin, Elena M. Comisión Nacional de Energía Atómica; Argentina